(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the psychological and pedagogical characteristics of teaching English to students in architecture and construction disciplines. It analyzes how cognitive, motivational, and professional factors influence language acquisition in technical university settings. The study highlights the importance of integrating discipline-specific content, visual learning strategies, and interactive methodologies to enhance communicative competence. The findings suggest that effective English language instruction for architecture and construction students requires a psychologically informed, professionally oriented, and pedagogically adaptive approach.